Use of psychiatric drugs in Dermatology, - Magda Blessmann Weber; Júlia Kanaan Recuero; Camila Saraiva Almeida (Sociedade Brasileira de Dermatologia, 2020)
Abstract Patients with psychocutaneous disorders often refuse psychiatric intervention in their first consultations, leaving initial management to the dermatologist. The use of psychotropic agents in dermatological practice, represented by antidepressants, antipsychotics, anxiolytics, and mood stabilizers, should be indicated so that patients receive the most suitable treatment rapidly. It is important for dermatologists to be familiar with the most commonly used drugs for the best management of psychiatric symptoms associated with dermatoses, as well as to manage dermatologic symptoms triggered by psychiatric disorders.